Dynamics Of Changes In Natriuretic Hormone During Immobilization Stress (Texas Journal of Medical Science, 2026)
This literature review examines in detail the effects of natriuretic hormones during immobilization stress and the dynamics of their changes. It also provides information on the types of natriuretic hormones and their influence on the activity of other hormones. Experiments conducted on this topic and their results are described. The findings show that significant changes in natriuretic hormone secretion occur at the early stages of immobilization stress, and this process is closely associated with cardiac activity and stress hormones. Additionally, the activation of the neuroendocrine system and the heart’s endocrine responses under stress were assessed